2022
DOI: 10.1021/acsaem.2c02243
|View full text |Cite
|
Sign up to set email alerts
|

Performance Degradation in Solution-Processed Cu2ZnSn(S,Se)4 Solar Cells Based on Different Oxidation States of Copper Salts

Abstract: The performance stability of Cu2ZnSn­(S,Se)4 (CZTSSe) solar cells is one of the key issues for its commercialization. Currently, Cu+ and Cu2+ salts have been successfully used to prepare CZTSSe solar cells, but comparative studies on the performance stability of the two types of solar cells are scarce. In this work, the performance degradation processes of CZTSSe solar cells, stored for 249 days under dry conditions, prepared respectively with Cu2+ and Cu+ salts (denoted Cu2+-cell and Cu+-cell, respectively) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since the PV parameters ( V OC , J SC , FF, and PCE) are widely known to be functions of electrical parameters ( J L , R Sh , R S , A , and J 0 ) [ 35 ] and the value of J L is influenced partly by the bandgap of CZTSSe absorber ( E g (CZTSSe)), therefore, it can be concluded that the E g (CZTSSe) affects the J L and thus the values of V OC , J SC , FF, and PCE. To investigate whether V doping in the Mo and MoSe 2 layers can affect E g (CZTSSe), as shown in Figure 6b, EQE measurements for the HCell‐Ref and HCell‐MoSe 2 :V were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Since the PV parameters ( V OC , J SC , FF, and PCE) are widely known to be functions of electrical parameters ( J L , R Sh , R S , A , and J 0 ) [ 35 ] and the value of J L is influenced partly by the bandgap of CZTSSe absorber ( E g (CZTSSe)), therefore, it can be concluded that the E g (CZTSSe) affects the J L and thus the values of V OC , J SC , FF, and PCE. To investigate whether V doping in the Mo and MoSe 2 layers can affect E g (CZTSSe), as shown in Figure 6b, EQE measurements for the HCell‐Ref and HCell‐MoSe 2 :V were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is useful to estimate contribution percentage of J L , R sh , R s , and ( A , J 0 ) to PCE for understanding influence mechanism of B doping and annealing on the PCE. The contribution percentages of change of J L , R sh , R s , and ( A , J 0 ) to change of PCE for the hcell‐0 to hcell‐0.1 and hcell‐0.1 to hcell‐0.1‐A‐O are calculated through combining contribution percentages of change of V oc , J sc , and FF to the change in PCE with that of change of J L , R sh , R s , and ( A , J 0 ) to changes of V oc , J sc , and FF, using data in Table 1 and 2 as well as the calculation approach reported by us, [ 42,43 ] as shown in Figure and Table S1–S5, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Electric parameters and J L of the hcell-0, hcell-0-A-O, hcell-0.1, and hcell-0. FF, using data in Table 1 and 2 as well as the calculation approach reported by us, [42,43] as shown in Figure 3 and Table S1-S5, Supporting Information. It is seen from Figure 3 and Table S1, Supporting Information, that the contribution percentages of the change in V oc , J sc , and FF to the increased PCE are 16.19%, 40.95%, and 42.86% respectively, for hcell-0 to hcell-0.1, and 35.29%, 22.94%, and 41.77%, respectively, for hcell-0.1 to hcell-0.1-A-O.…”
mentioning
confidence: 99%
“…104 Strategies, such as the valence state of tin, the different oxidation states of copper salts, and the regulation of element ratios, have also been applied to the absorbers by DMSO solvents. [105][106][107] Furthermore, Lin et al added DMF to the DMSO-based CZTS precursor solution to improve the wettability between the precursor and the Mo substrate, thereby improving the quality of CZTSSe absorbers; however, the highest conversion efficiency reached only 8.6% when the proportion of additive DMF is 20%. 108,109 Fortunately, Sun et al obtained more than 12% high-efficiency CZTSSe solar cells through the binary solvent engineering of DMF/DMSO in precursor solution in 2022.…”
Section: Aprotic Solventsmentioning
confidence: 99%